If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(1 + -7z) = -29 (1 * -4 + -7z * -4) = -29 (-4 + 28z) = -29 Solving -4 + 28z = -29 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 28z = -29 + 4 Combine like terms: -4 + 4 = 0 0 + 28z = -29 + 4 28z = -29 + 4 Combine like terms: -29 + 4 = -25 28z = -25 Divide each side by '28'. z = -0.8928571429 Simplifying z = -0.8928571429
| 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 | | 24x+9=21 | | 5x-7=4x-7 | | x/9-9=9 | | 9-(5a+1)+3a+7= | | -8h-6h=24 | | 4^3(8^(1/3)z^2 | | 6x+7y=-21 | | 3x+6(2)=x+11(4) | | 6x(2-3y)+7y=-21 | | 3ax-4x=0 | | 23=-3(5y+2) | | 66y/3-34y | | 8x^2-128x=0 | | 1+6y-15y= | | 1/3-K/8=7/24 | | -1(-1y+3)=1 | | -.4x^2+.2x=-2 | | 4x^2+10=-14x | | 2x^3/5=54 | | 3(x+4)+2x=2 | | 11-x=7+3x | | 5(0)-2=4-3(0)+2 | | 24=-3+6(v+7) | | 7(-3)+20=2(-3)+5 | | x^3=6x^2-36x-60 | | 7y^2-7=144 |